MULTI-YEAR DYNAMICS AND INFECTION RATE OF SCHIZOPHRENIA IN THE POPULATION AGED 18-90 IN THE ANDIJAN REGION OF THE FERGANA VALLEY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article is devoted to the analysis of the incidence of schizophrenia among the population of the Andijan region aged 18 to 90 years and its long-term dynamics. During a 40-year retro-prospective epidemiological study, significant changes in the indicators of primary morbidity of schizophrenia over the years were revealed. Despite annual variability, there was a steady trend towards a decrease in the overall incidence of schizophrenia among the region's population. The obtained data indicate the influence of various exogenous and social factors, as well as the effectiveness of preventive and diagnostic measures carried out in the healthcare system of the Andijan region. These results can be useful for improving strategies for early detection, prediction, and prevention of schizophrenia at the regional level.